Effectiveness of Criminal Offense Law Regarding Illegal Levies: Reforming Social Organizations within the Indonesian Legal Framework - Helmi, Muhammad Ishar; Pujiyono, Pujiyono; Zada, Khamami; Rambe, Mara Sutan; Sahid, Mualimin Mochammad (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
The widespread occurrence of illegal levies suggests that the current laws are ineffective in addressing extortion practices by mass organizations. This ineffectiveness stems from inadequate supervision of youth organization activities, insufficient transparency in financial transactions, and weak enforcement measures against organizations engaging in extortion. Actions taken by these organizations, such as coercing traders for illegal levies or soliciting donations, constitute criminal offenses under Article 368, paragraph (1) of the Criminal Code and are further underscored in Article 59, paragraph (2) of the law on Mass Organizations. This article aims to examine the challenges posed by the ineffectiveness of existing laws concerning criminal offenses related to illegal levies perpetrated by mass organizations and their members. The research employs a normative legal analysis, focusing on applicable legal rules and various doctrines to address specific issues. The methodologies utilized include statutory and conceptual approaches. The findings indicate that the current mass organization law is ineffective and requires revision, particularly regarding legal frameworks governing donation requests (illegal collections) made through coercive means. The sanctions imposed on mass organizations engaged in these practices are not criminal, rendering them ineffective. This article proposes the revision of Law No. 16 of 2017, which stipulates government regulations, to replace Law No. 2 of 2017, thus amending Law No. 17 of 2013 concerning community organizations.